2019
DOI: 10.1155/2019/4047617
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Intrathecal Chemotherapy in Adults: Single-Institution Experience in 109 Consecutive Patients

Abstract: Acute lymphoblastic leukemia and other aggressive lymphoid malignancies like Burkitt leukemia/lymphoma have high incidence of central nervous system (CNS) involvement. Various solid tumors, most notably breast cancer, can also metastasize into the CNS as a late stage complication causing devastating effects. Intrathecal (IT) chemotherapy consisting of methotrexate, cytarabine, or the two in combination is frequently used for the prophylaxis and treatment of CNS metastasis. Because of the high toxicity of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…The final sample consisted of nine men and six women with a mean age of 38.7 ± 8.1 years (range: 23 to 49). The findings showed that the safety features built into our study design, the use of non‐cutting needles, were effective at reducing adverse events to rates far below those reported in clinical settings 22,23 . There were no medically meaningful adverse events related to the drug formulation.…”
Section: Resultsmentioning
confidence: 74%
“…The final sample consisted of nine men and six women with a mean age of 38.7 ± 8.1 years (range: 23 to 49). The findings showed that the safety features built into our study design, the use of non‐cutting needles, were effective at reducing adverse events to rates far below those reported in clinical settings 22,23 . There were no medically meaningful adverse events related to the drug formulation.…”
Section: Resultsmentioning
confidence: 74%
“…Moreover, the preclinical results of intrathecal ASOs and adeno-associated viral (AAV) vector-mediated gene-delivery to CNS are promising in treatment other neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), dementia disease and spinocerebellar ataxia (1,(39)(40)(41)(42). Another field is neuro-oncology, where intrathecal chemotherapy may be associated with dose-related neurotoxic side effects (43,44).…”
Section: Implications Of Observed Csf Elimination Time Course the Present Observations Indicate Thatmentioning
confidence: 99%
“…Furthermore, its use is not recommended in the presence of hydrocephalus (because, due to impaired CSF flow, it augments the risk of neurotoxicity, furthering intracranial pressure and consequently brain herniation and ischemia) [ 4 , 22 , 33 ] or nodular disease only (due to limited diffusion of ITT agents into the subependymal tissue) [ 1 , 7 , 24 , 34 ]. ITT also involves invasive procedures and has possible serious adverse effects [ 24 , 29 , 35 ], even if it seems not to negatively affect quality of life [ 25 , 32 ].…”
mentioning
confidence: 99%